Correlating CT findings of stroke with hyperglycemia in acute ischemic stroke patients - Ameer Shaker (مجله كليه طب الكندي, 2019)
Background: Studies show that diabetic patients have a higher incidence of ischemic stroke than non-diabetic patients. In the Framingham study the incidence of thrombotic stroke was 25 times higher in diabetic men and 36 times higher in diabetic women than in those without diabetes